2011
DOI: 10.4028/www.scientific.net/amr.328-330.1734
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Flexural-Longitudinal Vibration in a Curved Periodic Pipe Conveying Fluid

Abstract: A longitudinal vibration coupling with a flexural vibration in a curved fluid-filled periodic pipe is studied. The pipe is fabricated by a periodic composite material structure based on the Bragg scattering mechanism of Phononic Crystals. Using the transfer matrix method, the band structure of an infinite periodic straight pipe is calculated, and the elastic wave propagation characteristics of the periodic pipe are discussed. Furthermore, the vibrational frequency response functions of a finite curved pipe are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Shen et al designed the conduit into a periodic structure and used the transfer matrix (TM) method to study the characteristics of steady-state waves in the system and the dynamic response of the periodic shell system. 27,28 It is found that the periodic conduit has better vibration damping performance than the aperiodic conduit. Yu et al 29 founded the existence of the Bragg and locally resonant band gaps, corresponding to the velocity field, can exist in a periodic pipe system through experiments and analyzed the influence of relevant factors on the band gaps .…”
Section: Introductionmentioning
confidence: 99%
“…Shen et al designed the conduit into a periodic structure and used the transfer matrix (TM) method to study the characteristics of steady-state waves in the system and the dynamic response of the periodic shell system. 27,28 It is found that the periodic conduit has better vibration damping performance than the aperiodic conduit. Yu et al 29 founded the existence of the Bragg and locally resonant band gaps, corresponding to the velocity field, can exist in a periodic pipe system through experiments and analyzed the influence of relevant factors on the band gaps .…”
Section: Introductionmentioning
confidence: 99%